Biophysical chemistry - Klostermeier, Dagmar, Markus G. Rudolph; Rudolph, Markus G.; Dagmar Klostermeier (Boca Ration CRC Press, 2017)
"Biophysical Chemistry explores the concepts of physical chemistry and molecular structure that underlie biochemical processes. Ideally suited for students of life sciences, but equally accessible to students and scientists in related fields, the book concisely describes the fundamental aspects of biophysical chemistry, and puts them into a biochemical context. The book is organized in four parts, covering thermodynamics, kinetics, molecular structure and stability, and biophysical methods. Cross-references within and between these parts emphasize common themes and highlight recurrent principles. End of chapter problems illustrate the main points explored and their relevance for biochemistry, enabling students to apply their knowledge and to transfer it to laboratory projects"--
Keywords: Physical biochemistry; Thermodynamics; Molecular structure